Studies on the reproductive Physiology of two critically endangered species of the North Adriatic Sea: Adriatic sturgeon (Acipenser naccarii) and European eel (Anguilla anguilla) - Mandelli, Michaela <1977> (Alma Mater Studiorum - Università di Bologna, 2016)
Reproductive physiology has many applications for a successful management of fish population in aquaculture. In particular the stock management of endangered species might take advantage of the knowledge concerning the reproductive cycle in order to improve the protocols and restore the population for restock activities. The Adriatic sturgeon (Acipenser naccarrii) and the European eel (Anguilla anguilla) are two endemic species of the North Adriatic Sea and are both listed in the the IUCN Red List of threatened species as “critically endangered”. Both the species nowadays rely on the experimental activities and new technologies that try to implement the farming conditions for an improvement of the population management for restocking purposes. In the present study the onset of puberty was investigated through plasma Testosterone analysis in A. naccarii. With reference to A. Anguilla the effect of photoperiod was assessed on the endocrine profiles during hormonal induction. Furthermore a new tank design has lead to spontaneous spawning that was then compared to the manual stripping protocol.